Strengthening the Internationalisation and Commercialization of Clusters and Cluster Organisations by Upgrading Managerial Competencies: Selected Cases from Poland and Lithuania - Pietrzykowski , Maciej (Studia Oeconomica Posnaniensia, 2016)
Clusters are no longer local or regional phenomena, being more and more often internationalized through affiliated companies in the cluster or by the behaviour of cluster organizations. The whole process is accelerated by new political concepts such as smart specialization as well as the striving for cluster consolidation and the concentration of financial support. In turn building strong cluster organizations requires the acquisition of skills to create added value for which the cluster members are willing to pay. Both processes of internationalization and commercialization require the acquisition of competences by the managers of clusters. The aim of this article is to analyse the level of competencies of cluster coordinators in Lithuania and Poland as far as the internationalisation and commercialization of clusters are concerned. These competencies influence cluster performance, both on the internal and international market. The survey results along with an analysis of the available cluster materials revealed the scale of the gap between the existing and desired competencies of cluster managers in both countries. The paper ends with a set of recommendations for cluster coordinators with the aim of strengthening the processes of internationalisation and commercializa- tion in clusters; thus building strong and effective cluster organisation as well.